Potentials of Blockchain Technology for Construction Management - Turk, Žiga; Klinc, Robert (Procedia engineering, 2017)
Blockchain technology enables distributed, encrypted and secure logging of digital transactions. It is the underlying technology of Bitcoin and other cryptocurrencies. Blockchain is expected to revolutionize computing in several areas, particularly where centralization was unnatural and privacy was important. In the paper, we present research on where and how this technology could be useful in the construction industry. The work is based on the study of literature on open issues that exist in construction process management. These are than matched to the capabilities of blockchain. We are motivated by the fact that construction projects involve a dynamic grouping of several companies. We study the degree to which the relationships among them are hierarchical or peer-to-peer and note that particularly in information intensive phases, centralization of information management was necessary because of technology. When using un-constraining technology, communication patterns among participants show a peer-to-peer nature of the relationships. In such environment, blockchain can provide a trustworthy infrastructure for information management during all building life-cycle stages. Even if building information modelling (BIM) is used, which assumes a centralized building information model, there is a role for blockchain to manage information on who did what and when and thus provide a basis for any legal arguments that might occur. On the construction site blockchain can improve the reliability and trustworthiness of construction logbooks, works performed and material quantities recorded. In the facility maintenance phase, blockchain's main potential is the secure storage of sensor data which are sensitive to privacy. We conclude that blockchain provides solutions to many current problems in construction information management. However, it is more likely that it will be built into generic IT infrastructure on top of which construction applications are built, rather than used directly by authors of construction related software. It has a potential to make construction processes less centralized which opens needs for research in that direction.